Association of hypertension and dyslipidemia with progression of DR (Diabetic Retinopathy). - Bharti, Sweta; Kumar, Amit (Student's Journal of Health Research Africa, 2025)
Background Diabetic Retinopathy (DR) is a major microvascular complication of Diabetes Mellitus (DM) and a leading cause of vision loss. Hypertension and dyslipidemia have been identified as modifiable risk factors that may accelerate DR progression. Methodology A hospital-based cross-sectional study was conducted among 200 diabetic patients at G.M.C.H., Purnea, from January to December 2024. Participants underwent clinical, ophthalmic, and laboratory evaluations. DR was graded using the ETDRS classification. Lipid abnormalities and hypertension were assessed as per standard guidelines. Data were analyzed using SPSS version 25 Results The prevalence of DR was 43%. Hypertension (61%) and dyslipidemia (54%) were significantly associated with DR (p < 0.05). Patients with both conditions showed a higher frequency of moderate-to-severe DR. Logistic regression revealed hypertension (OR 2.41, p = 0.006) and dyslipidemia (OR 1.97, p = 0.032) as independent predictors, with combined presence increasing risk more than threefold (OR 3.64, p = 0.002). Conclusion Hypertension and dyslipidemia are significant risk factors for the progression of diabetic retinopathy. Comprehensive management of blood pressure, lipid profile, and glycemic control is essential to reduce vision-threatening complications in diabetic patients. Recommendation Regular screening for lipid and blood pressure abnormalities should be integrated into diabetes care programs to prevent or slow DR progression.